Pengaruh Model Problem Based Learning (PBL) Terhadap Kemampuan Memecahkan Masalah Siswa Biologi pada Kelas X IPA di Madrasah Aliyah Swasta Miftahul Fallah Diski - Nabila Siregar; Khairuna Khairuna (BIOEDUSCIENCE, 2022)
Background: In the learning process, the teacher has not brought up the phenomena related to the material to find a solution. Such a learning process has not accompanied students to a problem that requires students to be able to formulate problems, formulate hypotheses, draw conclusions, and recommend problem-solving. This has an impact on the low problem-solving ability of students. This study aims to determine the effect of the Problem Based Learning (PBL) model on the problem-solving ability of Biology students in class X IPA-1 Madrasah Aliyah Swasta Miftahul Fallah Diski. Methods: The research method used is a quasi-experimental research design with One-Group-Pretest-Posttest. The data analyzed were in the form of pretest and post-test with data requirements test in the form of normality test and homogeneity test. Results: The results of the hypothesis test obtained the value of Sig. (2-tailed) in the "Equal variances assumed" section of 0.000 < 0.05, it can be. Conclusions: H0 is rejected, and Ha is accepted, which means that there is a positive and significant effect on students' problem-solving abilities in biology material. protists in class X IPA-1 SMA Madrasah Aliyah Private Miftahul Fallah Diski in the 2021/2022 academic year. PBL can increase the students' average pretest and post-test scores, where the average pretest score is 52.62 with a standard deviation of 7.352 and the post-test average value is 82.86 with a standard deviation of 6.036.